(untitled) (Mustansiria Dental Journal, 2024)
The purpose of this investigation was to evaluate the temperature rise inside pulp dentin channel preparation by twist drills . Twenty premolar tooth divided into two groups, each subdivided into 4 subgroup , si prepared the channels at 1.500 rpm/700 G by first & 5th uses of the drill, group B the channels at 30.000 rpm/50 G measuring the temperature rise inside the pulp , mmumed to prepared each channel . both groups there was temperature rise, but in group A ( slow speed) the iimr:1i;¤e:=.rtxre didn‘t reach to critical level (5.5 °C), while in group B this degree was wmtziistei ki some of specimen, also found the mean of temperature rise in case of 5th uses zore higher than the mean of the lst use in both groups . Tznperature rise inside the pulp during pin-hole preparation affected by speeds , tram rt;·i;Iy. sharpness of drill and also the diameter and the time consumed